Hubungan Tingkat Pengetahuan Ibu Dan Usia Pemberian Mp-Asi Dengan Kejadian Diare Pada Balita Wilayah Kerja Puskesmas Tampa Kabupaten Barito Timur : Relationship Between Level Of Maternal Knowledge And Age Of Feeding With Diarrhea Incidence In Toddlers, Tampa Health Center, East Barito - Alghifari, Muhammad; Lestarisa, Trilianty; Yuliani, Ni Nyoman Sri; Sasmithae, Lia; Balyas, Abi Bakring (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diarrhea is defined as a digestive disorder that has the characteristics of defecation 3 times or more during one day which produces a watery stool consistency and can be followed by blood. diarrhea cases that occurred in the East Barito area in 2019 were around 3,428 people for all ages and 1,584 toddlers. maternal knowledge and age of complementary feeding is one of the factors that cause diarrhea. The purpose of the study was to determine the relationship between the level of maternal knowledge and the age of complementary feeding with the incidence of diarrhea in toddlers. This research method is a cross sectional analysis with purposive sampling technique totaling 100 samples. Data were obtained through questionnaires. The results showed a percentage distribution of good knowledge level of 75%. The percentage of the age of giving MP-ASI is exactly 76%. Maternal knowledge and the incidence of diarrhea have a significant relationship with a p value of 0.001. Age of complementary feeding and the incidence of diarrhea have a significant relationship with a p value of 0.001. It is hoped that this research can be an evaluation material in health services.